Modulation of vascular reactivity in normal, hypertensive and diabetic rat aortae by a non-antioxidant flavonoid - Ajay, M.; Achike, F.I.; Mustafa, Mohd Rais (Elsevier, 2007)
In this study, we report the effects of a non-antioxidant ﬂavonoid ﬂavone on vascular reactivity in Wistar–Kyoto (WKY) rat isolated aortae.Whether ﬂavone directly modulates vascular reactivity in spontaneously hypertensive rat (SHR) and streptozotocin-induced diabetic-WKY rat isolated aortae was also determined. Thoracic aortic rings were mounted in organ chambers and exposed to various drug treatments in the presence of ﬂavone (10 M) or its vehicle (DMSO), which served as control. Pretreatment with ﬂavone enhanced relaxant effects to endothelium-dependent vasodilator acetylcholine (ACh) and attenuated contractile effects to 1-receptor agonist phenylephrine (PE) in WKY aortae compared to those observed in control aortic rings. Flavone had no effect on relaxations to ACh in WKY aortae incubated with either l-NAME or methylene blue, but enhanced relaxations to ACh in WKY aortae incubated with indomethacin or partially depolarized with KCl. Relaxations to ACh are totally abolished in both control or ﬂavone pretreated endothelium-denuded WKY aortae. Flavone attenuated the inhibition by -NADH of AChinduced relaxation in WKY aortae, but it had no signiﬁcant effect on the transient contractions induced by -NADH nor the pyrogallol-induced abolishment of ACh-induced relaxation in WKY aortae. Flavone enhanced endothelium-independent relaxation to sodium nitroprusside (SNP) in both endothelium-intact and -denuded WKY aortae. Flavone enhanced relaxation to ACh and SNP as well as attenuated contractile effects to PE in SHR and diabetic aortae, a ﬁnding similar to that observed in normal WKY aortae. From these results, we conclude that ﬂavone modulates vascular reactivity in normal as well as hypertensive and diabetic aortae. These effects of ﬂavone results probably through enhanced bioactivity of nitric oxide released from the endothelium.